Psychological impairments after ACL injury – Do we know what we are addressing? Experiences from sports physical therapists. (6th April 2021) - Piussi, Ramana; Krupic, Ferid; Senorski, Carl; Svantesson, Eleonor; Sundemo, David; Johnson, Urban; Hamrin Senorski, Eric
Abstract : Psychological impairments can follow an anterior cruciate ligament (ACL) injury and can impact the rehabilitation process. Our aim was to investigate experiences of sports physical therapists (PTs) in addressing psychological impairments in patients after ACL injury. We conducted four focus group interviews with fourteen sports PTs. The PTs' experiences of working with psychological impairments after ACL injury were summarized in four main categories: (1) "Calling for a guiding light", where PTs stated that the most common method of acquiring knowledge on addressing psychological impairments was through discussions with colleagues, and, at the same time, PTs expressed an insufficient knowledge of how to address psychological impairments; (2) "Meeting the burden of psychological impairments" where PTs stated that psychological impairments are greater than physical; (3) "Trying to balance physical and psychological aspects" where patient education and assessments were reported to be important in order to understand psychological impairments during rehabilitation; and (4) "Goal setting: a helpful challenge" where sports PTs expressed a need for specific knowledge of the rehabilitation of psychological impairments following ACL injury. To help provide the current best practice, we encourage researchers to develop psychologically centered interventions for rehabilitation after an ACL injury, and PTs to stay up‐to‐date with the literature published on the subject, including to implement eventual interventions.